KINERJA KARYAWAN DITINJAU DARI KOMPENSASI LANGSUNG DAN KOMPETENSI STUDI KASUS PADA PT. MANDIRI TUNAS FINANCE PALEMBANG - Tri Darmawati; Sherly Sherly; Tri Sinarti (MBIA, 2021)
This research aims to determine the effect of direct compensation and competence on employee performance at PT. Mandiri Tunas Finance Palembang. Distribution of questionnaires using google form with 56 respondents. The sampling method in this research uses a saturated sampling method. This research method uses an associative approach, which is looking for bonding patterns or patterns of influence between variables on one object, in order to recognize the influence between independent and dependent variables. The method of collecting information is a questionnaire. The variables studied were employee performance as the dependent variable, direct compensation and competence as the independent variable. Information that has been processed using the SPSS program produces a regression equation Y = 4,898+ 0.369X1 + 0, 503X2. Based on the results of the t test, it was found that tcount was 3.264 for direct compensation and 4.362 for competence so that direct compensation had a significant effect on employee performance and competence had a significant effect on employee performance. In addition, the f test results in 34,300 so that direct compensation and competence together have a significant effect on employee performance. Keywords: Direct compensation, competence, performance Abstrak Riset ini bertujuan mengetahui pengaruh kompensasi langsung dan kompetensi terhadap kinerja karyawan pada PT. Mandiri Tunas Finance Palembang. Penyebaran kuesioner memakai google form dengan 56 responden. Metode pengambilan sampel dalam riset ini memakai metode sampling jenuh. Metode riset ini memakai pendekatan assosiatif ialah, mencari pola ikatan atau pola pengaruh antar variabel pada satu objek, agar dapat mengenali pengaruh antar variabel bebas dan terikat. Metode pengumpulan informasi ialah, kuesioner. Variabel yang diteliti kinerja karyawan selaku variabel terikat, kompensasi langsung serta kompetensi selaku variabel bebas. Informasi yang sudah diolah dengan memakai program SPSS menghasilkan persamaan regresi Y= 4,898+ 0,369X1+ 0, 503X2. Berdasarkan hasil pada uji t diperoleh thitung 3,264 untuk kompensasi langsung dan 4,362 untuk kompetensi sehingga kompensasi langsung mempengaruhi signifikan terhadap kinerja karyawan serta kompetensi mempengaruhi signifikan terhadap kinerja karyawan. Selain itu pada uji f yang hasilnya 34,300 sehingga kompensasi langsung dan kompetensi secara bersama sama mempengaruhi signifikan terhadap kinerja karyawan. Kata Kunci: Kompensasi langsung, kompetensi, kinerja